Post a New Question

Algebra

posted by .

Why are these algebraic expressions used and explain the logical error: Since a = b, then a2 = a * b
Subtract b2 from both sides a2 – b2 = a * b – b2
Factor both sides: ( a + b )( a – b ) = b(a – b )
Divide both sides by ( a – b)
( a + b ) = b
Since a = b,

  • Algebra -

    error:
    since a-b = 0, you are dividing by zero !!!!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question